Methylation of the Corticotropin Releasing Hormone Gene Promoter in BeWo Cells: Relationship to Gene Activity. (17th September 2015) - Pan, Xin; Bowman, Maria; Scott, Rodney J.; Fitter, John; Nicholson, Richard C.; Smith, Roger; Zakar, Tamas
Abstract : Corticotropin releasing hormone (CRH) production by the human placenta increases exponentially as pregnancy advances, and the rate of increase predicts gestational length. CRH gene expression is regulated by cAMP in trophoblasts through a cyclic AMP-response element (CRE), which changes its transcription factor binding properties upon methylation. Here we determined whether methylation of the CRH proximal promoter controls basal and cAMP-stimulated CRH expression in BeWo cells, a well-characterized trophoblastic cell line. We treated the cells with 8-Br-cAMP and the DNA methyltransferase inhibitor 5-aza-2′ deoxycytidine (5-AZA-dC) and determined the effects on CRH mRNA level and promoter methylation. Clonal bisulfite sequencing showed partial and allele independent methylation of CpGs in the CRH promoter. CRH mRNA expression and the methylation of a subset of CpGs (including CpG2 in the CRE) increased spontaneously during culture. 8-Br-cAMP stimulated CRH expression without affecting the increase in methylation. 5-AZA-dC decreased methylation and augmented 8-Br-cAMP-stimulated CRH expression, but it blocked the spontaneous increase of CRH mRNA level. We conclude that the CRH promoter is a dynamically and intermediately methylated genomic region in BeWo cells. Promoter methylation did not inhibit CRH gene expression under the conditions employed; rather it determined the contribution of alternative cAMP-independent pathways and cAMP-independent mechanisms to CRH expression control.